VD_FINDINFO HC / 2014 / 314 vom 29. April 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, BAIL À LOYER, CAS CLAIR, PLACE DE PARC, PAIEMENT DE L'ARRIÉRÉ | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 257 CPC (CH), 319 CPC (CH), 319 let. a CPC (CH), 322 al. 1 CPC (CH)